Pengembangan LKS Beroreantasi HOTS Untuk Membekalkan Keterampilan Berpikir Tingkat Tinggi Siswa MAN Kelas 10 - Fadlun Fadlun; Rosmiati Rosmiati; Lis Suswati (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Bima, 2022)
The purpose of this study was to determine the feasibility of HOTS-based worksheets on Newton's Law material. This type of research uses research and development methods (Research and Development). The development model used in this research is the development of a learning system with the ADDIE model. ADDIE stands for Analysis, Design, Development or Production, Implementation or Delivery and Evaluation which was developed by Dick and Carry. This research was carried out at MAN 2. The research and development subjects consisted of 30 students of class X MAN Sape 2 Bima. In this study the assessment of the quality of instructional media was based on aspects including LKS expert instruments, material expert instruments, Physics subject expert instruments, and student instruments. The results of research and development of HOTS-oriented worksheets on Newton's Law material can be concluded (1) HOTS-oriented worksheets on Newton's Law material are developed through several stages, namely: determining the source of the book as a reference material, formulating basic competencies that must be mastered, designing worksheets, designing the appearance LKS from the front, back and contents, designing the contents of the LKS from the front cover, back cover and contents in accordance with HOTS, creating and searching for images and looking for practicums that match the material, determining attractive colors and images by adjusting the material, choosing learning material sources and packaging learning materials in accordance with HOTS, (2) HOTS-oriented worksheets on Newton's Law material that was developed and tested on student responses in product trials at MAN 2 Bima.